АLLEGORICAL IMAGES IN FOLK FABLES - Sydykova B. D.; Kanybek kyzy A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article discusses the formation of stable allegorical images in proverbs and sayings, and their significance in accurately reflecting various human character traits. Examples are provided, such as the fox, its cunning, deceit, beauty, and selfishness, or the wolf, its foolishness, greed, and tendency towards easy gain, as well as the cowardice of the hare, its insignificance, the grandeur of the lion, its strength and self-confidence, among others. Unlike other genres, such as epics or proverbs and sayings, proverbs and sayings have not been adequately collected or studied in folklore studies, which is one of the regrets in Kyrgyz literary scholarship. Some of these proverbs and sayings were reworked by poets and passed on to the people as their own versions. The article also attempts to explore the role and significance of the artistic devices and methods used to reveal various ideas in works of folk literature where allegorical images are present.